Backstepping Control Based on a Third-order Sliding Mode Controller to Regulate the Torque and Flux of Asynchronous Motor Drive - Zellouma, Dalal; Benbouhenni, Habib; Bekakra, Youcef (Periodica polytechnica. Electrical engineering and computer science, 2023)
This work represents a new nonlinear control for the asynchronous motor (AM) drive. The designed nonlinear control is based on the combination between the backstepping control (BC) scheme and third-order sliding mod control (TOSMC). In this proposed nonlinear control, the torque and flux are controlled. Also, the torque, current, and flux ripples are minimized by a proposed BC-TOSMC strategy. The proposed BC-TOSMC strategy is more robust compared to the field-oriented control (FOC). The proposed BC-TOSMC strategy of AM drive has been simulated in MATLAB/Simulink software. The comparisons were made between the proposed BC-TOSMC strategy and the FOC strategy under different operating conditions. The results show that the proposed BC-TOSMC strategy minimized the flux, current, and torque ripples of the AM drive compared to the FOC strategy, with a reduction torque ripples ratio of about 57.14%. Also, the total harmonic distortion (THD) values of stator current using the proposed BC-TOSMC strategy and FOC technique are respectively 1.09% and 3.42%. In this case, utilizing the proposed BC-TOSMC strategy, the performance of the AM has improved from the FOC strategy.